2003
DOI: 10.1182/blood-2002-06-1899
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 and pharmacodynamic studies of G3139, a Bcl-2 antisense oligonucleotide, in combination with chemotherapy in refractory or relapsed acute leukemia

Abstract: Overexpression of Bcl-2 is a potential mechanism for chemoresistance in acute leukemia and has been associated with unfavorable clinical outcome. We hypothesized that down-regulation of Bcl-2 would restore chemosensitivity in leukemic cells. To test this hypothesis, we performed a phase 1 study of G3139 (Genasense, Genta, Berkeley Heights, NJ), an 18-mer phosphorothioate Bcl-2 antisense, with fludarabine (FL), cytarabine (ARA-C), and granulocyte colony-stimulating factor (G-CSF) (FLAG) salvage chemotherapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(108 citation statements)
references
References 24 publications
5
101
1
1
Order By: Relevance
“…Based on several phase I/II clinical trials of AS Bcl-2, which were conducted to assess its safety, tolerance and therapeutic efficacy [23][24][25][26][27][28][29] on hematological malignancies and solid tumors, the first randomized phase III trial has been conducted for metastatic melanoma. The results were compared with dacarbazine and AS Bcl-2/dacarbazine.…”
Section: Effects Of Antisense Bcl-2 On Multiple Roles Of Bcl-2 R Kim mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on several phase I/II clinical trials of AS Bcl-2, which were conducted to assess its safety, tolerance and therapeutic efficacy [23][24][25][26][27][28][29] on hematological malignancies and solid tumors, the first randomized phase III trial has been conducted for metastatic melanoma. The results were compared with dacarbazine and AS Bcl-2/dacarbazine.…”
Section: Effects Of Antisense Bcl-2 On Multiple Roles Of Bcl-2 R Kim mentioning
confidence: 99%
“…In fact, previous studies indicated that treatment with AS Bcl-2 decreased Bcl-2 mRNA and/or protein levels up to 75% in different malignancies. 23,24,32,34 Others however have cited the fact that although downregulation of Bcl-2 was not observed, growth was inhibited 40 or that Bcl-2 expression in diagnostic tumor specimens was not predictive of Effects of antisense Bcl-2 on multiple roles of Bcl-2 R Kim et al response to this therapy. 24 In some of these reports, the assessment of Bcl-2 mRNA was more sensitive and reliable than the protein level.…”
Section: Effects Of Antisense Bcl-2 On Multiple Roles Of Bcl-2 R Kim mentioning
confidence: 99%
See 1 more Smart Citation
“…G3139 has been administered safely in combination with fludarabine, cytarabine, plus granulocytecolony stimulating factor (FLAG) to 20 patients with refractory AML or acute lymphoblastic leukemia (ALL). 77 Tolerable nausea, emesis, fever, fluid retention, and electrolyte imbalances were the main side effects encountered. bcl-2 mRNA levels were downregulated in 9 of 12 patients evaluated (75%); the CR rate was 35%.…”
Section: Induction Of Apoptosismentioning
confidence: 99%
“…bcl-2 mRNA levels were downregulated in 9 of 12 patients evaluated (75%); the CR rate was 35%. 77 Apoptosis also may be enhanced by activating the caspase cascade through blockade of the IAPs and through inhibition of the nuclear factor B (NF B) pathway (using I B kinase inhibitors or proteasome inhibitors) and the PI3K pathway (using kinase inhibitors). 78 IAPs, including the X-linked inhibitor of apoptosis (XIAP), can block apoptosis through interaction with members of caspase family.…”
Section: Induction Of Apoptosismentioning
confidence: 99%